HUBUNGAN TINGKAT RELIGIUSITAS TERHADAP INTENSITAS KENAKALAN REMAJA ANAK SEKOLAH DI SMK YBKP3 GARUT - Shalahuddin, Iwan; Yamin, Ahmad; Sumarna, Umar (Jurnal Kesehatan, 2021)
Juvenile delinquency among high school students is the result of those who have issues in mental or psychological development. The aim of this study is to relationship between religiosity and intensity of juvenile delinquency among high school students. This study used quantitative approach and the design applied was product-moment correlation. For bivariate analysis purposes, one-way ANOVA was used to test compare mean. The total population of this study was 387 teenage students who have both good and bad behavior in terms of religiosity. The instrument used had been valid with the value of point biseral correlation from 0.126 to 0.617 with the alpha of 0.05. The reliability value obtained was alpha 0.80. The results showed that there was no difference between the religious level and the anger level based on the student’s age (P-value) = 0.967, student class (0.976) and gender (0.991). The conclusion obtained is that the religious level of students obtained is high or good as many as 192 students (49.6%). This shows that the subject believes and believes in things that are fundamental and dogma in religion. Recommendations are given to always maintain well-applied arrangements, and need to be developed to correct all deficiencies and mistakes in an effort to prevent delinquency among school children.